Efficiency Enhancement of Organic Light-Emitting Diodes on Flexible Substrate With Patterned Inverted Conical Structure - Yi-Jun Wang; Jian-Gang Lu; Han-Ping D. Shieh (IEEE Photonics Journal, 2016)
The total internal reflection effect in conventional electroluminescent devices causes a large amount of light energy to be trapped in devices and induces heat energy that adversely affects the performance of the device. To enhance the light outcoupling efficiency without sacrificing the electrical properties, a patterned inverted conical (PIC) structure fabricated by a focused femtosecond laser on a flexible substrate was demonstrated. Compared with the conventional flexible organic light-emitting diode (OLED), the OLED with the PIC structure exhibited a current efficiency increase of a factor of 2.6 with no emission spectrum altered. In addition, the flexible OLED with PIC substrate can avoid the mirror reflection effect under the strong ambient light for a better visual experience. This highly effective method is compatible with the current device fabrication process and is applicable for full-color OLED display and lighting.